Effect of Salt Stress on Germination and Early Seedling Growth in Lentil - Varalakshmi,; Das, Arpita; Bhattacharya, Sudip; Pramanik, Krishnendu; Senapati, B. K. (International Journal of Economic Plants, 2025)
The present study was conducted during December, 2018–February, 2019, to assess the genetic variation and association of the characters concerning germination and seedling parameters with salt tolerance index and subsequently evaluate the five varieties of lentil as per their response against varied level of salinity during early seedling stage at laboratory condition. Salinity poses a significant challenge to crop productivity worldwide, affecting various physiological and metabolic pathways in crops like lentils, particularly in arid and semi-arid regions where lentils are commonly cultivated. Seeds of five varieties of lentil were grown at four different levels of salinity (0, 50, 100 and 150 mM NaCl) in completely randomized block design (CRD) with factorial combination. The germination percentage, shoot length, root length, shoot: root ratio, seedling fresh weight, seedling dry weight and seedling vigour index were studied and data were recorded. Results revealed that most of the studied traits reflected significant genetic variation. High heritability coupled with high genetic advance was detected for most of the traits and confirmed the importance of selection for improving the traits. Salinity levels drastically reduced seedling vigour and other parameters with increasing salt concentration. The degree of diminution varied with different varieties. Among the five varieties, Ranjan was detected as salt tolerant followed by Moitree and ILL-6002 was identified as most sensitive to salinity. Ranjan can be considered as a valuable genetic resource for lentil breeding programme under salt stress situation.